Differences in symptom severity and gait balance deficit in concussed adolescents with and without concussion history. Issue 11 (25th May 2017) - Chou, Li-Shan; Peterson, Quinn; Osternig, Louis
Abstract : Objective: There is conflicting evidence on whether a prior concussion is associated with a prolonged recovery course. This study was aimed to examine the effect of concussion history on recovery of symptoms and gait balance control in adolescents. Design: A prospective, repeated-measures design was employed. Subject were assessed within 72 hours of sustaining a concussion and at 2, 4, and 8 weeks post-injury. Settings: University research laboratory Participants: High school student athletes with concussion injury Outcome measures: Symptoms resulting from the injury were assessed using a 22 symptom inventory adapted from the Standardised Concussion Assessment Tool. Dual-task gait testing was employed to examine how divided attention affects balance control following concussion. Comparisons between subjects with and without concussion history were made for dependent variables of symptom scores and medial-lateral motion of the center-of-mass. Main Results: A total of 31 concussed adolescents were tested, 9 of them had 1 or 2 diagnosed concussions more than 12 months prior to the current injury. Four subjects without concussion history and 4 subjects with concussion history were not permitted to resume normal physical activities within our 2-month study period. Subjects with concussion history displayed significantly elevated symptom scores during the first two weeks of recovery and displayed greater gait instability during the first month of recovery when compared to subjects without concussion history. Conclusions: These preliminary findings indicate that previous concussion, more than one year prior to the current injury, could affect deficit severity and length of recovery. Competing interests: The authors have no conflicts of interest to declare.